Testing the evidence of purchasing power parity for ASEAN-5 countries using panel estimation / Abdul Rahim Ridzuan and Elsadig Musa Ahmed - Ridzuan, Abdul Rahim; Musa Ahmed, Elsadig (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
This article examines the validity of purchasing power parity (PPP) hypothesis using panel methods for five founding members of the Association of Southeast Asian Nations (ASEAN) in US dollar and Japanese yen. A range of heterogeneous panel unit root tests and panel cointegration analysis used in literature applied to test long run PPP for post Bretton Woods floating period (1980-2007). This study shows that a sequence of unit root tests does not favor mean reversion and found mixed result for Singapore. This outcome, however, might be due to generally limited power of conventional classical unit root test. Nevertheless, the PPP proposition seems to hold for post financial crises period (post-1997) in US and Japan as base country. Consequently, this study is broadly consistent with Baharumshah et al. (2007) results, invariant to numeraire currency, of mean reversion, mainly supporting PPP for Asian crises era. Furthermore, present study has used recent developed heterogeneous panel cointegration tests and found significant cointegration between nominal exchange rate, domestic and foreign prices. However, the results provide more evidence for ASEAN-5 in Japanese based in favor of cointegration in long run compared with US dollar is the numeraire currency.